Determinants of bone mineral density in young and premenopausal females: influence of body mass index, vitamin D, and parathormone hormone - Sahar A Elsayed; Omar M.M Mohafez; Hanan Sayed M Abozaid (Wolters Kluwer Medknow Publications, 2021)
Background and aim Vitamin D deficiency is a challenging health problem in premenopausal females that negatively affects bone mineral density (BMD). Low BMD in premenopausal women is related to lifestyle, vitamin D insufficiency, and secondary hyperparathyroidism. So, we aimed to evaluate BMD in young and premenopausal females and its relation with vitamin D, parathormone (PTH), BMI, and lifestyle factors. Patients and methods A total of 86 young and premenopausal females were included, and BMD, serum calcium, vitamin D, PTH, BMI, and lifestyle were determined. Results Z score of the spine showed that 26.7% of the patients were below expected. According to T score, 30% were osteopenic, and 9% were osteoporotic. Overall, 59.3% had vitamin D deficiency, and 20.9% had insufficiency. Patients with below expected BMD, osteopenic, and osteoporotic had significantly low vitamin D and BMI and high PTH. Spine and hip-BMD and spine T and Z scores were positively correlated with BMI and vitamin D and negatively correlated with PTH. Hip T and Z scores were positively correlated with BMI and vitamin D. PTH was negatively correlated with vitamin D and BMI. Spine and hip BMDs were positively correlated with sunlight exposure and physical activity but negatively correlated with carbonated and caffeinated beverage consumption and family history of osteoporosis. Conclusion Low BMD is a challenging health problem in young and premenopausal females, which may be related to low BMI, vitamin D deficiency, and lifestyle factors in the form of inadequate sunlight exposure, excessive consumption of caffeinated and carbonated beverages, and decreased physical activity, in addition to hyperparathyroidism and positive family history of osteoporosis.